PENERAPAN SANKSI HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA PECURIAN HEWAN TERNAK - Cut Nurita (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The criminal act of theft is still a dilemma, and this seems a quite serious problem which requires any solution. The problems in this study are what factors cause the theft of livestock, and how the implementation of criminal legal sanctions is against the perpetrators of theft.This study uses descriptive methods through normative approach (legal research), which is based on the facts in the field approach to the problem, and is carried out by examining various legal aspects in terms of applicable regulations.The finding shows that the factors that cause the theft of livestock are economic factors, low appreciation to religion, family factors, environmental / social factors, unemployment,  influence of mass media either TV or foreign films, influence of alcohol, and opportunity factor . In addition to these factors, there are objective factors and subjective factors. The implementation of criminal legal sanctions for the perpetrators of the theft is regulated in Article 363 of the Criminal Code. Keywords: Criminal Act, Theft,  Livestock